Evaluation and Pathologic Classification of Choledochal Cysts: Clinicopathologic Analysis of 84 Cases From the West. (May 2021) - Aydin Mericöz, Cisel; Hacihasanoglu, Ezgi; Muraki, Takashi; Pehlivanoglu, Burcin; Memis, Bahar; Mittal, Pardeep; Polito, Humbert; Saka, Burcu; Everett, Rhonda; Sarmiento, Juan; Kooby, David; Maithel, Shishir K.; et al.
Abstract : Choledochal cyst (CC) is believed to be a mostly Asian disorder. As a clinically defined entity, its pathologic correlates are poorly characterized. Eighty-four resected CCs from the West were reanalyzed. After applying established Japanese criteria, 9/66 with available imaging were disqualified and 10/39 with preoperative cyst typing had to be recategorized. None had been diagnosed with, or evaluated for, pancreatobiliary maljunction, but on retrospective analysis of radiologic images, 12/66 were found to have pancreatobiliary maljunction. The clinical findings were: F/M=5.7; mean age, 48; most (77%) presented with abdominal pain; mean size, 2.9 cm; choledocholithiasis 11%. Gross/histologic examination revealed 3 distinct pathology-based categories: (I) Cystic dilatation of native ducts (81%). (II) Double bile duct (13%), almost all of which were found in women (10/11); all were diagnosed by pathologic examination, and not preoperative diagnosis. (III) Gastrointestinal (GI) duplication type (6%). Microscopic findings of the entire cohort included mucosal-predominant lymphoplasmacytic inflammation (50%), follicular cholangitis (7%), mucosal hyperplasia (43%; 13% with papillae), intestinal metaplasia (10%), BilIN-like hyperplasia (17%), erosion/ulceration (13%), and severe dysplasia-mimicking atypia including "detachment atypia" and micropapillary degeneration (11%). Carcinomatous changes were seen in 14 cases (17%) (high-grade dysplasia/carcinoma in situ in 7, intraductal papillary neoplasm 1, and invasive carcinoma 6); and 13/14 of these occurred in pathologic category I, all with cyst size >1 cm. In conclusion, diagnostic imaging guidelines used in Asia are not routinely used (but should be adopted) in the West. Pathologically, cases designated as CC are classifiable in 3 groups: category 1 (dilated native duct type), more prone to carcinomatous change; category 2, double-duct phenomenon (all but 1 being female in this study); and category 3, GI-type duplication. Overall, 17% of CCs show carcinomatous change (50% of them invasive). CC specimens should be carefully examined with this classification and submitted entirely for assessment of at-risk mucosa and cancerous transformation.